Improving the conductivity and dimensional stability of anion exchange membranes by grafting of quaternized dendrons. Issue 14 (11th April 2022) - Wei, Xiangtai; Wu, Jianrong; Jiang, Hao; Zhao, Xinsheng; Zhu, Yuanqin
Abstract: High conductivity is critical for the practical applications of anion exchange membranes (AEMs) in fuel cells. In this study, a new strategy for enhanced conductivity and dimensional stability of AEMs by incorporating quaternized dendrons is proposed. Thanks to the introduced quaternized dendrons, distinct nanoscale phase separation and well‐connected ion conductive channels are formed in the as‐prepared membranes (PPO‐QG‐x). As a result, PPO‐QG‐x AEMs achieve high hydroxide conductivities up to 65.5 mS cm −1 at 20 °C and 121.5 mS cm −1 at 80 °C (IEC = 1.95 mmol g −1 ), while possessing good dimensional stability. Meanwhile, PPO‐QG‐x AEMs show good alkaline stability with the maximum loss in conductivity of 15.1% after treated in 2 M NaOH at 80 °C for 960 h. In addition, the single‐cell assembled with PPO‐QG‐12 membrane exhibit a peak power density of 249.4 mW cm −2 at 60 °C. Overall, this work provides a new insight to achieve high conductivity of AEMs. Abstract :